Baler – A Need Based Technology for Rice Straw Management - Sharma, Ankit; Bhattu, Bharat Singh; Singh, Gurdeep (Indian Farming, 2015)
The commercially available machines help in easy collection of loose paddy straw which can later be used in several ways like composting, energy generation and raising of mushrooms etc. These machines are especially useful for multi-purpose Co-operative Societies/Agro Service Centers for collecting and baling rice straw in the combine harvested fields on custom hiring basis. It can be adopted at large scale for straw management as it cleans the field for sowing of next crop with additional income to the farmers by the sale of baled straw to the industries.